2023
DOI: 10.1002/ece3.10715
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity of a generalist fish species resident to lotic environments: Insights from the Great Lakes region

Claire Hetzel,
Patrick Forsythe

Abstract: Fish morphology is incredibly plastic and local/resident morphology can be influenced by factors including habitat, predation, resource availability, and water velocity. Through analysis of body shape using geometric morphometrics, we describe the degree of phenotypic plasticity within a generalist fish species resident to low‐order tributaries of Green Bay and Lake Michigan. We predicted that isolated populations of creek chub (Semotilus atromaculatus) would display plastic responses in body shape due to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…This finding is similar to the results of a previous study by Pashkov et al [28], who reported significant differences (p < 0.05) in the morphometrics and body colors of geographically distinct populations. Compared with those of other vertebrates, the morphological characteristics of fish are more susceptible to the influence of the environment [29,30]. Morphological differences among the same fish species are closely related to habitat type and quality [31].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to the results of a previous study by Pashkov et al [28], who reported significant differences (p < 0.05) in the morphometrics and body colors of geographically distinct populations. Compared with those of other vertebrates, the morphological characteristics of fish are more susceptible to the influence of the environment [29,30]. Morphological differences among the same fish species are closely related to habitat type and quality [31].…”
Section: Discussionmentioning
confidence: 99%